In Silico Prediction of Multitarget Mechanism of Quinoline and Its Analogs on Phosphoinositide-3-Kinase Pathway Proteins - Nyaipriya Devi Sanglakpam (International Journal of Molecular Biotechnological Research, 2023)
Objective: Phosphoinositide 3-kinases (PI3Ks), the target of rapamycin (PI3K/Akt/mTOR, PAM), are a family of enzymes that play a role in the growth, proliferation, differentiation, motility, survival, and intracellular trafficking of cells, all of which are essential for healthy cellular function and are also connected to cancer. In this study, quinoline and its derivatives were employed to analyze its inhibition activity on the phosphoinositide-3-kinase pathway. Methods: In this work, eight phytocompounds from quinoline were chosen, and the phosphoinositide-3-kinase pathway was analyzed to assess their multitarget mechanism. The study was carried out computationally utilizing PubChem as a data source and the molecular structures of the phytocompounds, as well as Indian medicinal plants, phytochemistry, and treatments. For the pharmacological evaluation of these drugs under the ADME properties for toxicity prediction, several additional approaches were applied. Results: The docking data revealed that eight analogs of quinoline were the most potent inhibitors for the proteins, Akt PBD 3MV5, PDK1 3RWQ, PIK3 3S2A, and mTOR-4DRI. Conclusion: All these bioactive compounds could be regarded as worthy candidates for the inhibition of the phosphoinositide-3-kinase pathway due to their high affinity for the protein.
Keywords: 3MV5 protein; 3RWQ protein; 3S2A protein; 4DRI protein; Phosphoinositide 3-kinase pathway; multitarget mechanism; quinoline